2021
DOI: 10.3390/cancers13071514
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Inequalities and Ethnicity Are Associated with a Positive COVID-19 Test among Cancer Patients in the UK Biobank Cohort

Abstract: We explored the role of socioeconomic inequalities in COVID-19 incidence among cancer patients during the first wave of the pandemic. We conducted a case-control study within the UK Biobank cohort linked to the COVID-19 tests results available from 16 March 2020 until 23 August 2020. The main exposure variable was socioeconomic status, assessed using the Townsend Deprivation Index. Among 18,917 participants with an incident malignancy in the UK Biobank cohort, 89 tested positive for COVID-19. The overall COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…However, these studies did not examine individual risk in the context of community-level impacts [ 12 , 13 ]. A recent study of 18,917 participants in the UK Biobank showed that ethnic minority background and community-level socioeconomic status assessed by the Townsend Deprivation Index are important COVID-19 risk factors among individuals with cancer [29] . Our analysis provides robust results that address this gap by concurrently examining personal exposure to COVID-19, occupation, and comorbid conditions, and community-level socioeconomic factors on a population scale using participant information not commonly available in registry or hospital-based cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies did not examine individual risk in the context of community-level impacts [ 12 , 13 ]. A recent study of 18,917 participants in the UK Biobank showed that ethnic minority background and community-level socioeconomic status assessed by the Townsend Deprivation Index are important COVID-19 risk factors among individuals with cancer [29] . Our analysis provides robust results that address this gap by concurrently examining personal exposure to COVID-19, occupation, and comorbid conditions, and community-level socioeconomic factors on a population scale using participant information not commonly available in registry or hospital-based cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Many focused on large established cohorts like UK Biobank that could rapidly link to data on SARS-CoV-2 testing (34), COVID-19 hospitalization (35) and mortality (36). Since then, many risk factors have been reported, including smoking (37, 38, 39, 40, 41, 42), diabetes (38, 43, 44, 45), asthma (46, 47) and vitamin D (48, 49) as predisposing to worse outcomes. We compared our results to the literature on COVID-19 in UK Biobank to identify any differences to standard approaches and find new insights.…”
Section: Resultsmentioning
confidence: 99%
“…8 11 12 Similarly, scholars have been called to shift their research focus from solely describing inequalities towards analysing processes that are amenable to change and identifying implementable solutions that help advance social and equity agendas. 10 11 …”
Section: Discussionmentioning
confidence: 99%
“…This situation has led international organisations and governments to review and reinforce their cancer strategies posing central attention on reducing inequalities, particularly among historically marginalised populations 8 11 12. Similarly, scholars have been called to shift their research focus from solely describing inequalities towards analysing processes that are amenable to change and identifying implementable solutions that help advance social and equity agendas 10 11…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation